2012
DOI: 10.2196/resprot.2136
|View full text |Cite
|
Sign up to set email alerts
|

Mobile.net: Mobile Telephone Text Messages to Encourage Adherence to Medication and to Follow up With People With Psychosis: Methods and Protocol for a Multicenter Randomized Controlled Two-Armed Trial

Abstract: BackgroundSchizophrenia is a high-cost, chronic, serious mental illness. There is a clear need to improve treatments and expand access to care for persons with schizophrenia, but simple, tailored interventions are missing.ObjectiveTo evaluate the impact of tailored mobile telephone text messages to encourage adherence to medication and to follow up with people with psychosis at 12 months.MethodsMobile.Net is a pragmatic randomized trial with inpatient psychiatric wards allocated to two parallel arms. The trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…For those studies including comparison groups control interventions comprised treatment as usual (TAU) (Glynn et al, 1990;Spaniel et al, 2008a;Rotondi et al, 2010;Yakirevitch et al, 2010;Spaniel et al, 2012) and videos and information about schizophrenia treatment (Steinwachs et al, 2011). Five studies were conducted in the United States (Han et al, 2008;Glynn et al, 2010;Rotondi et al, 2010;Steinwachs et al, 2011;Granholm et al, 2012;Gottlieb et al, 2013), 5 in Europe (Spaniel et al, 2008a;Anttila et al, 2012;Spaniel et al, 2012;Välimäki et al, 2012;van der Krieke et al, 2012), 1 in Australia (Alvarez-Jimenez et al, 2013) and 1 in Israel (Yakirevitch et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…For those studies including comparison groups control interventions comprised treatment as usual (TAU) (Glynn et al, 1990;Spaniel et al, 2008a;Rotondi et al, 2010;Yakirevitch et al, 2010;Spaniel et al, 2012) and videos and information about schizophrenia treatment (Steinwachs et al, 2011). Five studies were conducted in the United States (Han et al, 2008;Glynn et al, 2010;Rotondi et al, 2010;Steinwachs et al, 2011;Granholm et al, 2012;Gottlieb et al, 2013), 5 in Europe (Spaniel et al, 2008a;Anttila et al, 2012;Spaniel et al, 2012;Välimäki et al, 2012;van der Krieke et al, 2012), 1 in Australia (Alvarez-Jimenez et al, 2013) and 1 in Israel (Yakirevitch et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Sims et al (2012) found that text message appointment reminders to a total of 2817 subjects was associated with a 25-28% reduction in missed outpatient clinic appointments. Välimäki et al (2012) described methodology for a 12 month trial of text messages about medications, appointment, and self-care for inpatients on antipsychotics. The use of Internet-enabled mobile devices and social networking technologies to promote exercise in subjects at a specialist first-episode psychosis treatment center is also being investigated.…”
Section: Questionmentioning
confidence: 99%
“…Several previous studies have investigated the prevalence of cell phones, computers, and/or Internet use, as well as the acceptability and efficacy technology-based interventions in patients with schizophrenia (described in Table 1). Improved missed appointment rates, medication adherence, and prodromal and other symptom assessment have been shown in studies using SMN or text-based applications on cell phones for individuals with schizophrenia Ben-Zeev et al, 2014;Montes et al, 2012;Palmier-Claus et al, 2012Sims et al, 2012;Välimäki et al, 2012). Certain aspects and patterns of an Internet profile and SMN use could be related to schizophrenia spectrum disorders (Krishna et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…The research project ‘Mobile.Net’ (Välimäki et al . ) was conducted in psychiatric hospital organizations where the healthcare professionals worked.…”
Section: Methodsmentioning
confidence: 99%
“…The study is a part of the ‘Mobile.Net’ (ISRCTN: 27704027) project, evaluating the effects of text messages on improving patient adherence to treatment (Välimäki et al . ). While aiming to develop and evaluate the effects of a newly developed mobile intervention, we wanted first to ensure that this intervention will target patient focused real problems in treatment adherence (Russell et al .…”
Section: The Studymentioning
confidence: 97%